An assessment of in-service teachers’ confidence and challenges of integrating technology in Tanzanian secondary schools - Loisulie, Paul; Kondo, Tabu S. (S&Co Publishing, 2025)
The integration of technology in education has become a global priority, with the potential to enhance teaching and learning outcomes. In Tanzania, efforts have been made to incorporate digital tools into secondary education to enhance instructional effectiveness. However, the successful adoption of technology largely depends on teachers’ confidence and their ability to overcome various challenges. This study assesses Tanzanian secondary school teachers’ confidence in using technology and the challenges they face in its integration. Using an online survey design, data were collected from teachers across different regions. Two hundred and three (N=203) in-service teachers responded to the online survey in which 80% are male. The findings indicate that prior to the intervention, 49.3% of respondents rated their ICT skills as